Recovering from drought and conflict - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
During the 1991-92 growing season southern Africa suffered the worst drought this century. Throughout much of the region rainfall was insufficient for sowing crops. Even when there was some rain, it was not enough to mature the crop. By Februarv...